Hubungan Antara Kondisi Lingkungan Rumah Dengan Kejadian Penyakit ISPA Pada Anak Balita Di Wilayah Kerja Puskesmas Sario Kecamatan Sario Kota Manado - Winardi, William; Umboh, Jootje M.L.; Rattu, A. Joy M. (JIKMU, 2015)
Penyakit ISPA masih menjadi salah satu masalah kesehatan masyarakat yang penting untuk diperhatikan karena merupakan penyakit akut dan bahkan dapat menyebabkan kematian pada balita di berbagai negara berkembang termasuk negara Indonesia yang kaya akan penduduk yang masih taraf di bawah ekonomi. Angka kejadian penyakit ISPA nasional pada tahun 2010 sebesar 758 per seribu penduduk pada usia balita dan 16 provinsi mengalami Kejadian Luar Biasa (KLB) ISPA dengan Case Fatality Rate (CFR) sebesar 7,16%. Angka Case Fatality Rate (CFR) penderita penyakit ISPA pada tahun 2012 ialah sebesar 8,45% dimana angkanya mengalami peningkatan dari tahun 2011 bertambah sebanyak 1200 menjadi 8852 penderita ISPA. Tujuan penelitian ini adalah untuk mengetahui hubungan antara kondisi lingkungan rumah (jenis lantai, jenis dinding, luas ventilasi, tingkat kepadatan hunian dalam rumah, status merokok, dan status hewan peliharaan di dalam rumah) dengan kejadian penyakit ISPA pada anak balita di Wilayah Kerja Puskesmas Sario Kecamatan Sario Kota Manado. Sumber data primer diperoleh dari kuesioner dan sumber data sekunder dari instansi terkait. Analisa data menggunakan uji Chi-Square. Dari hasil didapatkan bahwa terdapat hubungan yang signifikan antara ventilasi kamar, tingkat kepadatan hunian dalam satu rumah, status merokok, dan status hewan peliharaan di dalam rumah; dan faktor yang paling dominan berhubungan adalah status merokok di dalam rumah. Kata Kunci : Kondisi Fisik Rumah, Kejadian Penyakit ISPA pada balita. Abstract Acute Respiratory Tract Infections (ARTI) disease is still to be one of public health problem most important to attention because as a acute disease and can make mortality rate to children in the most of are going developed country including Indonesian that rich of public are still low economic. The most vulnerable age suffered by the respiratory disease are children under five age still low immune resistance during infancy. ISPA is one of the diseases associated with the environment in house, especially the conditions very close to the refuge of the environment in house. Environment in house is very closely interact on a day-to-day living in infants, when the environment in house where a family gathering place and shelter unhealthy because of an attack by bacterial or viral infection that can cause a variety of diseases in infants one is ARI. Research aims to analysis relationship between the house environment conditions (type of floor, type of wall, room ventilation, rate of population in one house, statue of smoked cigarette, and statue of pets wild in house) with ARTI disease incidence on children under five ages. This research using observational type with cross sectional design by descriptive and this research doing by analytical design. The research sample was got it by simple randomized sampling. Research location in the working areas of Sario Health Centre of the Sario District of Manado City, and conducted by November 2014 until January 2015 year. This research of population is all of children under five ages which on going on Sario Health Centre of the Sario District of Manado City that have had positive result by doctor was check it have ARTI disease, while the responden is parenteral from the baby of children under five ages. This sample research was done by simple randomized sampling with Lemeshow formulae to populating the biggest as amount 88 respondents. The source of primary data was obtained from questionnaires and secondary data was from Sario Health Centre of the Sario District of Manado City. The data analysis was done using Chi-Square test and multiple logistic regression test. The data analysis was done using SPSS version 17. Result showed that’s significant relationship between the statue of smoking in house, occupancy density in house, room ventilation, and statue pets wild in house with disease of ARTI on children under five ages, while the type of floor and the type of wall did not have a significant relationship with disease of ARTI on children under five ages. From this result of research can be conclude that the house environment conditions with disease incidence of ARTI (Acute Respiratory Tract Infections) on children under five ages in working areas of Sario Health Centre of the Sario District of Manado City have a significant relationship. To proposed the Health Government of Manado City could be given health education about dangerous and impact of smoked. Keywords : The House Environment Factors, Incidence of Acute Respiratory Tract Infections on Children Under Five Ages